Encyclopedia of television theme songs - Robinson, Mark A. 1973- (McFarland, 2011)
"Featuring 1,000 detailed entries, this encylopedia examines the phenomenon of television theme songs. Organized alphabetically by TV series from The A-Team to Zorro, the individual themes are designated by title, composer, lyricist and performer. Each entry also includes the series' cast credits, its network, the years of its original run, and an in-depth program description"--Provided by publisher